Spatial Shift-Share Analysis as a Tool for Studying the Economic Development of Russia’s Macroregions - Kotov, Alexandr V. (Economy of Regions, 2021)
Structural analysis of regional economies plays a significant role in political decision-making. In the context of Russian regional development, a new research topic emerges at the level of economic macroregions as defined in the current Spatial Development Strategy of the Russian Federation. The present work aims to empirically evaluate the use of shift-share analysis to clarify the contribution of the neighbourhood effect in addition to national and regional growth factors. The proposed approach incorporates structural shifts of spatial interactions into the classical method using various matrices (adjacency, neighbourhood). Macroregional economic growth was decomposed on the basis of consolidated sectoral structural dynamics and national development stages from 2004-2018 to reveal specific features of structural growth. It was determined that the most significant effects at all stages are those generated by national economic policy. Regional effects are especially important for macroregions whose development is characterised by substantial state support combined with an adequate resource base. Negative values of the spatial sectoral shift persisting across all macroregions testify to the positive mutual influence of macroregional specialisation and intensified interregional cooperation. Sectoral effects were observed only for particular economic sectors or at certain macroregional development stages. Recommendations for strengthening interregional interactions are proposed on the basis of the enlarged typology of structural effects in macroregions. Comparative analysis confirmed the consistency of estimates obtained using standard and spatial shift-share methods. Future research will focus on clarifying the structure of spatial relationships and detailing actual interregional economic interactions in the form of products and goods exchanged between macroregions.